Applying link grammar formalism in the development of English-Indonesian machine translation system - N., Zamin; B., Baharudin; T.B., Adji (2008)

(untitled)
In this paper, we present a Machine Translation (MT) system from English to Indonesian by applying Link Grammar (LG) formalism. The Annotated Disjunct (ADJ) technique available in the LG formalism is utilized to map English sentences into equivalent Indonesian sentences. The ADJ is a promising technique to deal with target languages that do not have grammar formalism, parser, and corpus available like Indonesian language. An experimental evaluation shows that the applicability of LG for Indonesian language worked as expected. We have also discussed some significant issues to be considered in future development. Â© 2008 Springer-Verlag Berlin Heidelberg.